Descemet's membrane rupture associated with forceps delivery: A narrative review on diagnosis and management (Research, Society and Development, 2025)
Neonatal corneal opacity (NCO) is an ophthalmologic emergency that severely threatens visual development. Among its causes, obstetric trauma, particularly from forceps delivery, remains a significant, though decreasing, etiology. This trauma can cause a rupture in Descemet's membrane (DM), leading to acute corneal edema, high astigmatism, and a profound risk of irreversible amblyopia. This narrative review aims to synthesize the most recent scientific evidence (2020-2024) on the approach to NCO, focusing on the clinical, imaging, and management findings that differentiate traumatic DM ruptures from their main clinical mimics. Methods: A narrative review was conducted, searching PubMed, SciELO, and LILACS for publications from 2020 to 2024 using relevant descriptors. Results: The synthesized literature indicates that any unilateral corneal clouding in a newborn with a history of instrumented delivery mandates urgent investigation. The classic differential diagnosis is primary congenital glaucoma (PCG). Clinical examination reveals that forceps-induced tears are typically vertical or oblique, whereas Haab's striae (from PCG) are horizontal or circumferential. Tools like Anterior Segment Optical Coherence Tomography (AS-OCT) are essential for confirming the presence, location, and extent of the DM tear or detachment. Management is time-sensitive and ranges from conservative (topical hypertonics) to surgical (descemetopexy with air/gas) or, in refractory cases, keratoplasty (PKP or DSAEK). Conclusion: The approach to neonatal corneal opacity requires rapid etiological clarification. The ophthalmologist plays a central role in using clinical history and advanced imaging (AS-OCT) to distinguish traumatic from congenital causes, a distinction that dictates immediate management and the critical, long-term strategy for amblyopia prevention.